1997
DOI: 10.1021/jm9607360
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid and Synthetic Chlorogenic Acid Derivatives:  Novel Inhibitors of Hepatic Glucose-6-phosphate Translocase

Abstract: The enzyme system glucose-6-phosphatase (EC 3.1.3.9) plays a major role in the homeostatic regulation of blood glucose. It is responsible for the formation of endogenous glucose originating from gluconeogenesis and glycogenolysis. Recently, chlorogenic acid was identified as a specific inhibitor of the glucose-6-phosphate translocase component (Gl-6-P translocase) of this enzyme system in microsomes of rat liver. Glucose 6-phosphate hydrolysis was determined in the presence of chlorogenic acid or of new synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
194
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(208 citation statements)
references
References 42 publications
12
194
1
1
Order By: Relevance
“…Therefore, if a similar mechanism accounted for glucose release on the serosal side of the epithelial cells, transport should be inhibited by the chlorogenic acid derivative S4048, which blocks the glucose-6-phosphate translocase within the membrane of the endoplasmatic reticulum (24,25). In perfused intestine from wild-type mice, increasing concentrations of S4048 only slightly decreased glucose absorption (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if a similar mechanism accounted for glucose release on the serosal side of the epithelial cells, transport should be inhibited by the chlorogenic acid derivative S4048, which blocks the glucose-6-phosphate translocase within the membrane of the endoplasmatic reticulum (24,25). In perfused intestine from wild-type mice, increasing concentrations of S4048 only slightly decreased glucose absorption (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that, in a separate pharmacological study, each extract (leaf, stem, root and fruit) elicited a range of in vitro anti-diabetic activities (Martineau et al, 2006), it is interesting that all the identified classes of phenolic compounds, chlorogenic acid, quercetin derivatives, procyanidins and anthocyanins, have demonstrated anti-diabetic potential in vitro and in vivo (Hemmerle et al, 1997;Rodriguez de Sotillo and Hadley, 2002;Kim et al, 2003;Tsuda et al, 2003;Pinent et al, 2004;Ajay et al, 2005;Coskun et al, 2005;Dias et al, 2005;Jayaprakasam et al, 2006 …”
Section: Figurementioning
confidence: 99%
“…A major advance was derived from the cloning of murine and human glucose-6-phosphatase by Chou and co-workers [20,42] and the finding that the glucose-6-phosphatase gene is normal in patients suffering from glycogen storage disease types 1b and 1c [43]. Progress on a parallel path came with the development of a new class of highly specific high-affinity inhibitors of the glucose-6-phosphatase system that act exclusively on microsomal glucose 6-phosphate transport while leaving the enzymic phosphohydrolase activity unchanged [12][13][14][15][16][17][18]. Thus there now is convincing molecular evidence in favour of the substrate transport model of glucose-6-phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…Photoaffinity probes S 0957 and S 1743 ( Figure 1) were synthesized in accordance with the procedures described [12,13].…”
Section: Photoaffinity Probesmentioning
confidence: 99%
See 1 more Smart Citation